2023
DOI: 10.1039/d3md00157a
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of indole-modified tamoxifen relatives as potent anticancer agents

Abstract: Modulation of existing drugs is an attractive strategy to achieve improved activity in cancer therapy by lowering their effective dose. Preparation of relatives has been suggested and explored to improve...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…[4,5] Indole was first synthesized in 1866 by German scientist Adolf von Baeyer, and its derivatives have been studied as potential cancer-inhibiting agents. [6] Several studies have found that certain indole derivatives have anti-cancer effects and may suppress the proliferation of breast cancer cells. [7][8][9] 3,3'diindolylmethane (DIM), which is derived from indole-3-carbinol (I3 C), are found in cruciferous vegetables [10][11][12] has been shown to possess anti-proliferative, pro-apoptotic and anti-angiogenic effects in breast cancer cells by modulating estrogen metabolism, which is relevant in hormone receptor-positive breast cancers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4,5] Indole was first synthesized in 1866 by German scientist Adolf von Baeyer, and its derivatives have been studied as potential cancer-inhibiting agents. [6] Several studies have found that certain indole derivatives have anti-cancer effects and may suppress the proliferation of breast cancer cells. [7][8][9] 3,3'diindolylmethane (DIM), which is derived from indole-3-carbinol (I3 C), are found in cruciferous vegetables [10][11][12] has been shown to possess anti-proliferative, pro-apoptotic and anti-angiogenic effects in breast cancer cells by modulating estrogen metabolism, which is relevant in hormone receptor-positive breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Indole was first synthesized in 1866 by German scientist Adolf von Baeyer, and its derivatives have been studied as potential cancer‐inhibiting agents [6] . Several studies have found that certain indole derivatives have anti‐cancer effects and may suppress the proliferation of breast cancer cells [7–9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation